Laparoscopic treatment of pericardial effusion. Fifteen years of experience - Ricci, Luis; Alvarado Figueroa, José; Martino, Silvina; López, Priscilla; Herrando, Ignacio; Rechiman, Ingrid; Staltari, Daniel (Revista Argentina de Cirugía, 2021)
Background: massive pericardial effusion causes potentially fatal hemodynamic compromise of the cardiac function. When medical therapy fails, invasive treatment seeks to treat the prevailing pathology and its recurrence. Treatment alternatives include invasive percutaneous pericardial drainage, subxiphoid pericardial window, pericardium-pleural and pericardial-peritoneal window. The pericardial-peritoneal laparoscopic window results in equal or better results compared to other variants, with the benefits of minimally invasive surgery. Objective: to analyze the experience of 15 years in the treatment of massive pericardial effusion by a peritoneal pericardium. Method: the same two surgeons did all the procedures. Direct communication between the pericardial and peritoneal space in patients with massive pericardial effusion without cardiac tamponade was performed. Exclusion criteria included patients with signs of cardiac tamponade who did not respond to draining pericardiocentesis, as well as those who did not tolerate pneumoperitoneum, with laparotomy in the upper abdomen or inadequate exposure of the phrenic center. Results: there were 58.8% of women. Mean age was 66.7 years. Previous history of cardiovascular disease 86.3% and oncologic disease 47%. Draining pericardiocentesis 68.6%. A.S.A III 70.6%. Mean operative time 31 minutes. 6 days of hospital stay. Intraoperative morbidity 3,92%. Postoperative morbidity 13,7%. Mortality 1,9%. Effusion recurred 1.9%. Survival at 30 days 90%.Follow-up, mean 31.2 months. Conclusions: the pericardial-peritoneal laparoscopic window is a simple, effective and safe procedure with low morbidity an recurrence rate.